Shape Optimization Design of Brake System Based on Opti Struct - CHEN Zai-fa (Journal of Harbin University of Science and Technology)
Due to friction heat effect or severe vibration and other factors，the performance of automobile brake is insufficient，according to natural frequency theory of the principle of dynamics，Firstly，the simulation software of OptiStruct is used to analyze the disc brake pads with different material properties，Secondly，the pre deformation of brake disc is defined based on HyperMorph and used as the design variable of shape optimization，through the OptiStruct optimization solver to calculate the best shape of disc brake disc type，Finally，the sensitivity of the design variables is analyzed，and the design variables which have the greatest impact on the optimization results are given. The design results are significant to improve the performance of brake system，reduce braking noise and reduce vibration.